Catalyst-free synthesis of oxazol-2(3H)-ones from sulfilimines and diazo compounds through a tandem rearrangement/aziridination/ring-expansion reaction - Song, Lina; Tian, Xianhai; Han, Chunyu; Amanpur, Mehran; Rominger, Frank; Hashmi, A. Stephen K. (Organic chemistry frontiers, 2021)
Oxazol-2(3H)-ones play a significant role in the fields of organic synthesis and drug development. The classical synthesis of oxazol-2(3H)-one derivatives requires high temperatures, metal catalysts, complex substrates or multi-step reactions. We report a concise synthesis of oxazol-2(3H)-ones from readily available diazo compounds and sulfilimines through a tandem rearrangement/aziridination/ring-expansion reaction in the absence of any catalyst and additive. This reaction is scalable and the obtained products were readily converted to other valuable aza-heterocyclic frameworks.